VENTILATION SHAFT DESIGN IN ENHANCING INDOOR AIR MOVEMENT FOR PUBLIC BUILDING - Wahab, Izudinshah Abd; Bakar, Noor Athirah Abu; Amin, Noor Dina Md; Hamberi, Mohd Jamil Mohd (Journal of Sustainable Technology and Applied Science (JSTAS), 2023)
The conditions of dense built environment, land topography and the needs on having deep-plan buildings seems inevitable nowadays. The situations give a poor impact on building indoor natural ventilation. Therefore, the application of stack ventilation strategy has become more important. This is due to the limitation of natural cross ventilation potential. This paper presents a design proposal strategy based on the research aim to provide a good natural ventilation for a new proposed Waterfront Marina & Club building in Penang. Based on stack effect ventilation strategies as references, the project introduced an atria like ventilation shaft with consideration of the building oreantation based on the site context. As the sea breeze is coming from the East side of the building, the shaft is designed open facing the direction to act as wind catcher before transporting the air movement vertically through the shaft. At lower levels, the air movement is spread to all other spaces connected to the main corridor. The shaft is not only depending on the sea breeze but may also functioned as stack effect throat to move the air vertically due to the difference of air pressure via the levels.